2016
DOI: 10.1021/acs.langmuir.6b01591
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Surface Manipulation Using Orthogonal Click Chemistry

Abstract: Polymer brushes are excellent substrates for the covalent immobilization of a wide variety of molecules due to their unique physicochemical properties and high functional group density. By using reactive microcapillary printing, poly(pentafluorophenyl acrylate) brushes with rapid kinetic rates toward aminolysis can be partially patterned with other click functionalities such as strained cyclooctyne derivatives and sulfonyl fluorides. This trireactive surface can then react locally and selectively in a one pot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…SuFEx was used to “click” a silyl ether rapidly and quantitatively to a polymer containing native SO 2 F groups . Since dye‐modified polymers have been widely used in a range of biological applications including fluorescent sensors, probes, and agents for cell imaging, Disperse Red 1 was selected as a model small molecule dye for attachment at the polymer chain‐ends and quantification of the SuFEx click reaction.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…SuFEx was used to “click” a silyl ether rapidly and quantitatively to a polymer containing native SO 2 F groups . Since dye‐modified polymers have been widely used in a range of biological applications including fluorescent sensors, probes, and agents for cell imaging, Disperse Red 1 was selected as a model small molecule dye for attachment at the polymer chain‐ends and quantification of the SuFEx click reaction.…”
Section: Resultssupporting
confidence: 88%
“…The SuFEx reaction has become recognized as a superior approach for postpolymerization modification in polymer synthesis, surface functionalization, and other forms of polymer materials engineering. For example, the SuFEx reaction was recently used by Locklin and co‐workers for the postmodification of polymer brushes on surfaces . These studies demonstrated that SuFEx can be used to introduce other types of click functionalities into polymer scaffolds.…”
Section: Introductionmentioning
confidence: 99%
“…The Popik group reported a cyclopropenone‐masked dibenzocyclooctyne (DIBO) that undergoes clean decarbonylation under ultraviolet A (UV‐A) irradiation to afford DIBO . They have also demonstrated the application of these cyclooctyne precursors in the surface functionalization of patterned polymer brush films . However, derivatization of AuNPs or Au surfaces with cyclopropenone‐masked DIBO moieties has never been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[37] They have also demonstrated the applicationo ft hese cyclooctyne precursors in the surfacef unctionalization of patterned polymer brush films. [38][39][40][41] However, derivatization of AuNPs or Au surfaces with cyclopropenone-masked DIBO moieties has never been reported. Such masked cyclooctynes are unreactivet owards azides or nucleophiles in the absence of UV light, thus making it the ideal precursor for incorporation onto AuNPs to overcome the limitations previously described.…”
Section: Introductionmentioning
confidence: 99%
“…μCP was also used to conjugate amines through aminolysis on polyester brushes. As the amines carried an additional and orthogonal reactive group, the polymer surface could be modified in a second post‐modification step . In another study, μCP on polymer brushes was used to control the surface patterning at defined distances by variation of the printing pressure …”
Section: Introductionmentioning
confidence: 99%